The Italian strategy to fight illegal treatment with growth promoters: Results of the 2017-2019 histological monitoring plan - Marzia Pezzolato; Elisa Baioni; Cristiana Maurella; Alessandro Benedetto; Elena Biasibetti; Elena Bozzetta (Italian Journal of Food Safety, 2022)
The Histological Control Plan has been introduced in Italy in 2008 as an indirect monitoring tool of illicit administration of sexual hormones and corticosteroids in bovine. Analysis of 2008-2016 results permitted to draw a new plan targeting risk category. This work presents the results of the histopathological monitoring plan that was carried out from 2017 to 2019. The overall prevalence of samples suspected of treatment with corticosteroid was 11.3% [95% confidence interval (CI) 6.6-17.8] in 2017; 10.2% (95% CI 6.6-16.9) in 2018 and 8.9% (95% CI 4.6-15.4) in 2019. The overall prevalence of samples suspected of treatment with sexual hormones was 2.3 % (95% CI 0.5-6.6) in 2017; 6.2% (95% CI 2.7-11.8) in 2018 and 12.4% (95% CI 7.4- 19.1) in 2019. Although not targeting and measuring specific molecules, this strategy allows to verify the trend of illicit treatments and identify farms to be submitted to further check.